2018
DOI: 10.1093/humrep/dey264
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies mutations in FSIP2 as a recurrent cause of multiple morphological abnormalities of the sperm flagella

Abstract: This work was supported by the following grants: the 'MAS-Flagella' project financed by the French ANR and the DGOS for the program PRTS 2014 (14-CE15) and the 'Whole genome sequencing of patients with Flagellar Growth Defects (FGD)' project financed by the Fondation Maladies Rares for the program Séquençage à haut débit 2012. The authors have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 55 publications
5
95
0
1
Order By: Relevance
“…Until now, only a few gene autosomal variants have been reported to cause MMAF phenotype in infertile man, such as AKAP4 , DNAH1 , CFP43 , CFP44 and FISP2 . Among these genes, DNAH1 is believed to be the main genetic contributor .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only a few gene autosomal variants have been reported to cause MMAF phenotype in infertile man, such as AKAP4 , DNAH1 , CFP43 , CFP44 and FISP2 . Among these genes, DNAH1 is believed to be the main genetic contributor .…”
Section: Discussionmentioning
confidence: 99%
“…The genetic characterization of this phenotype began in 2014 with the identification of DNAH1 (dynein axonemal heavy chain 1) as a major gene implicated in MMAF . After the development and the introduction of high throughput sequencing (HTS) techniques such as whole exome sequencing (WES), deleterious mutations were formally identified in eight additional MMAF genes ( AK7 , ARMC2 , CFAP43 , CFAP44 , CFAP69 , FSIP2 , TTC21A , and WDR66 ) showing the high genetic heterogeneity of this phenotype. Despite these important advances in gene identification, about half of the MMAF cases remain idiopathic without a genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that the MMAF phenotype is associated with genetic mutations. Previous studies revealed that mutations in DNAH1 (MIM: 603332), DNAH2 (MIM: 603333), AKAP4 (MIM: 300185), CCDC39 (MIM: 613798), AK7 (MIM: 615364), CFAP251 (MIM: 618146), CEP135 (MIM: 611423), FSIP2 (MIM: 615796), ARMC2 (MIM: 611226), QRICH2 (MIM: 618304), SPEF2 (MIM: 610172), CFAP69 (MIM: 617949), CFAP43 (MIM: 617558) and CFAP44 (MIM:617559) could cause the human MMAF phenotype . However, more research is needed to reveal the etiology of the remaining 30%–40% of MMAF cases.…”
Section: Introductionmentioning
confidence: 99%